Le renouvellement urbain à Annaba, entre recherche d’équité territoriale et tendance à la gentrification - Bahia Kebir; Anissa Zeghiche (Cybergeo, 2022)
This article highlights the issues of urban renewal in major Algerian cities, through a case study in the precarious district of El M'Haffeur in Annaba, a city in eastern Algeria. This paper confronts the search for territorial equity, through requalification of marginalized spaces, with the realities of a gentrification process that occurs on pericentral spaces according to market opportunities. The article demonstrates that the device for the reduction of precarious housing looks like a legitimizing tool to free up land coveted by private real estate developers who are the main actors in this gentrification. The evicted inhabitants, whose words are recorded and analyzed in this article, express a strong feeling of injustice finding themselves forced to give up for their right to housing and against their right to the city.